2022
DOI: 10.3390/foods11121756
|View full text |Cite
|
Sign up to set email alerts
|

Why Being ‘Stressed’ Is ‘Desserts’ in Reverse—The Effect of Acute Psychosocial Stress on Food Pleasure and Food Choice

Abstract: The link between acute stress, food pleasure and eating behavior in humans by employing measures of individual reward mechanisms has not been investigated as of yet. Having these insights is key to understanding why many people experience a change in eating behavior when experiencing stress. Thirty-five Danes (mean age 21.71 years) underwent a stress-inducing and relaxation-inducing task based on a randomized cross-over study design. Both tasks were combined with the Leeds Food Preference Questionnaire, to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…Furthermore, several papers have reported that chronic stress is linked to a change in diet towards fewer main meals and higher intake of, especially, highly-palatable snack foods, mainly due to a continued activation of the HPA axis [16,64]. In line with these studies and a previous study on acute stress reporting an increase in the unconscious craving for high-fat sweet snack foods [41], the majority of respondents reported to have increased their intake of sweet snacks after being ill with stress, and a large group likewise reported to have increased their intake of salty snacks.…”
Section: The Effect Of Chronic Stress On Appetite Meal Patterns and F...supporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, several papers have reported that chronic stress is linked to a change in diet towards fewer main meals and higher intake of, especially, highly-palatable snack foods, mainly due to a continued activation of the HPA axis [16,64]. In line with these studies and a previous study on acute stress reporting an increase in the unconscious craving for high-fat sweet snack foods [41], the majority of respondents reported to have increased their intake of sweet snacks after being ill with stress, and a large group likewise reported to have increased their intake of salty snacks.…”
Section: The Effect Of Chronic Stress On Appetite Meal Patterns and F...supporting
confidence: 69%
“…Previous research by the authors of the present article has shown that acute psychosocial stress, reward, and food choice are linked via specific reward measures [41]. More specifically, it was found that 'implicit wanting' as a measure of unconscious craving towards specific food types increased for high-fat sweet foods when under the influence of acute psychosocial stress.…”
Section: Purpose Of This Studysupporting
confidence: 46%
See 1 more Smart Citation
“…Thus, these aspects all provided pleasure for both groups and thus attested to the fact that the intrinsic product characteristics of food may operate as the foundation for a pleasurable experience. These results mirror those found in previous studies by the current authors [ 27 , 28 , 35 , 58 ], as well as confirm findings in the literature in the field of food satisfaction and wellbeing, which have found a strong relation between the sensory properties of food and satisfaction and liking [ 59 , 60 ]. In addition, the aspects of fulfilling one’s ‘Needs’ and ‘Expectations’ and having ‘Choices’ were also among the most chosen for both groups.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study found that people suffering from chronic stress indeed show signs of anhedonia and report changes in appetite, the perception of food pleasure, and eating behavior [ 27 ]. In addition, it was discovered that even short bouts of acute psychosocial stress have the potential to alter individuals’ food preferences by the specific reward mechanism of implicit wanting, leading to the choice of highly palatable foods [ 28 ]. Thus, it can be argued that people suffering from stress, even in short temporary events, likewise experience symptoms of anhedonia [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%